Aggregate and distributional effects of increasing taxes on top income earners - Bettina Brüggemann; Jinhyuk Yoo (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2015)
We analyze the macroeconomic implications of increasing the top marginal income tax rate using a dynamic general equilibrium framework with heterogeneous agents and a fiscal structure resembling the actual US tax system. The wealth and income distributions generated by our model replicate the empirical ones. In two policy experiments, we increase the statutory top marginal tax rate from 35 to 70 percent and redistribute the additional tax revenue among households, either by decreasing all other marginal tax rates or by paying out a lump-sum transfer to all households. We find that increasing the top marginal tax rate decreases inequality in both wealth and income but also leads to a contraction of the aggregate economy. This is primarily driven by the negative effects that the tax change has on top income earners. The aggregate gain in welfare is sizable in both experiments mainly due to a higher degree of distributional equality.
Keywords: E21; E62; H21; H24; 330; Top Income Taxation; Heterogeneous Agents; Incomplete Markets; Income and Wealth Inequality